THE OPTIMIZING OF STUDENT'S MATHEMATICAL THINKING SKILLS THROUGH MATEMATIKA NALARIA REALISTIK IN MATHEMATICS OLYMPIAD TRAINING AT MADRASAH IBTIDAIYAH - Rusdin Rusdin; Rusli Rusli (Al-Bidayah : jurnal pendidikan dasar Islam, 2020)
This study aimed to select and identify Madrasah Ibtidaiyah (MI) Students' at Sorong City having mathematical Olympiad skills using Matematika Nalaria Realistik (MNR) Learning Model. Through this model, it will be analysed students' mathematical thinking skills, including mathematical comprehension skills, mathematical communication skills, and mathematical reasoning skills. The subject of this research was 33 students in 5th grade and two students in 6th grade at MI Sains Al-Hidayah Sorong City. This study applied the design research method with three phases, namely, preliminary design, teaching experiment, and retrospective analysis. Data on students' mathematical thinking skills were obtained through pre-test and post-test using descriptive analysis in each phase. Results of this study in the preliminary design involving 35 students were obtained pre-test (1) average was 9,74; (2) standard deviation was 15.72. The results of the teaching experiment phase were obtained post-test (1) average was 13,57; (2) standard deviation was 13,75; and (3) an increase of 39,32%. The results of the retrospective analysis involving 7 students were obtained pre-test (1) average was 38,28; (2) standard deviation was 23,09. In the post-test was obtained (1) average was 72,28; (2) standard deviation was 9,81; and (3) an increase of 88,77%. Thus MNR model contributed significantly to improve students' mathematical thinking skills. From 7 students participating in the final phase, three students had good skills, and four students had moderate skills